What is the Form of Protecting Customary Land in Indonesia? A Study of the History and Construction of Settings - Widyorini Indriasti Wardani (PDIH Untag Semarang, 2023)
This article examines the legal protection for customary land rights based on forest law in Indonesia. The study of customary land is important because customary land is the communal ownership of land subject to customary law. Policies related to customary land rights are inseparable from regulations regarding forestry law because customary rights appear starting with the clearing of forests by customary law communities. Forestry management after Indonesia’s independence cannot be separated from government legal politics, especially related to forestry law in Indonesia. This writing departs from the question of how the history of the existence of customary land and how the protection of customary land in the regulation of forestry law in Indonesia. The writing of this article uses a normative juridical method, namely studying material using theory from literature books, including scientific writing in journals and material related to laws. Based on the hypothesis, forestry regulations in Indonesia have not provided legal protection for customary lands and have even eliminated the existence of customary land itself, which is the source of life for indigenous peoples. The lack of protection can cause conflicts between the government and indigenous peoples, one of the factors due to the government’s takeover of customary land ownership from indigenous peoples. With Government Regulation Number 23 of 2021 concerning the Management of Forest Areas, which also regulates customary forests as separate forest groups (not included in state forests), customary forests are recognized.